Exploring Heterogeneous NoC Design Space in Heterogeneous GPU-CPU Architectures - 方娟 冷镇宇 刘思彤 姚治成 隋秀峰 (Journal of computer science and technology, 2015)
Computer architecture is transiting from the multicore era into the heterogeneous era in which heterogeneous architectures use on-chip networks to access shared resources and how a network is configured will likely have a significant impact on overall performance and power consumption. Recently, heterogeneous network on chip （NoC） has been proposed not only to achieve performance comparable to that of the NoCs with buffered routers but also to reduce buffer cost and energy consumption. However, heterogeneous NoC design for heterogeneous GPU-CPU architectures has not been studied in depth. This paper first evaluates the performance and power consumption of a variety of static hot-potato based heterogeneous NoCs with different buffered and bufferless router placements, which is helpful to explore the design space for heterogeneous GPU-CPU interconnection. Then it proposes Unidirectional Flow Control （UFC）, a simple credit-based flow control mechanism for heterogeneous NoC in GPU-CPU architectures to control network congestion. UFC can guarantee that there are always unoccupied entries in buffered routers to receive flits coming from adjacent bufferless routers. Our evaluations show that when compared to hot-potato routing, UFC improves performance by an average of 14.1% with energy increased by an average of 5.3% only.